Effects of glucagon-like peptide-1 on the differentiation and metabolism of human adipocytes. - El-Bekay, Rajaa; Coín-Aragüez, Leticia I.; Fernandez-García, Diego; Oliva Olivera, Wilfredo; Bernal-López, María Rosa; Clemente-Postigo, María Mercedes; Delgado-Lista, Javier; Díaz-Ruiz, Alberto; Guzmán-Ruiz, Rocio; Vázquez-Martínez, Rafael; Lhamyani, Said; Roca-Rodríguez, María del Mar; et al. (British Pharmacological Society, 2016)
Glucagon-like peptide-1 (GLP-1) analogues improve glycaemic control in type 2 diabetic (T2D) patients and cause weight loss in obese subjects by as yet unknown mechanisms. We recently demonstrated that the GLP-1 receptor, which is present in adipocytes and the stromal vascular fraction of human adipose tissue (AT), is up-regulated in AT of insulin-resistant morbidly obese subjects compared with healthy lean subjects. The aim of this study was to explore the effects of in vitro and in vivo administration of GLP-1 and its analogues on AT and adipocyte functions from T2D morbidly obese subjects.
https://v2.sherpa.ac.uk/id/publication/6832
Keywords: Péptidos; Obesidad - Aspectos moleculares; Tejido adiposo; Obesity; Adipocyte; Glucagon-Like Peptide 1 (GLP1)